Controls of precipitation and vegetation variability on the NE Tibetan Plateau during the late Pliocene warmth (~3.5-3.0 Ma) - Schwarz, FLorian; Salzmann, Ulrich; Koutsodendris, Andreas; Nie, Junsheng; Friedrich, Oliver; Ni, Jian; Garzione, Carmala; Fang, Xiaomin; Wu, Fuli; Woodward, John; Appel, Erwin; Pross, Jörg (Global and planetary change, 2022)
To better understand precipitation variability in a warmer-than-present world with elevated atmospheric CO2 concentrations, this study presents high-resolution palynological and element geochemical analyses of a late Pliocene drill core (3.5-3.0 Ma) from the today hyperarid Qaidam Basin on the north-eastern Tibetan Plateau. Quantitative rainfall estimates based on modern pollen-climate transfer functions indicate a 10-fold higher annual rainfall during the mid-Piacenzian Warm Period (mPWP; 3.264-3.025 Ma) than today, with values of 300-400 mm/a. Throughout the late Pliocene, the Qaidam Basin was covered with a temperate semi-desert shrubland. Varying percentages of the local lakeshore vegetation and long-distance arboreal pollen, as well as fluctuations in carbonate-silicate geochemistry, indicate a highly variable rainfall. Our study suggests that precipitation in the northern Qaidam Basin was primarily controlled by an East Asian Monsoon system (EAMS) that was located further north than today. Spectral analysis of the Artemisia/Chenopodiaceae (A/C) pollen ratio indicates an orbitally controlled cyclicity with a strong link between moisture availability and insolation forcing. A decline in precipitation before the end of the mPWP at ca. 3.15 Ma is likely to be linked to cooling in the North Atlantic and initial Northern Hemisphere ice-sheet build-up. Our study identifies NH insolation and ice-sheet advances as major controls of the late Pliocene variability and strength of the EAMS in semi-arid NW-China.